Research on Application Operation Development of Space-Integrated-Ground Information Network - Qiang MEI; Nan SHI; Yanxiao LI; Xionghong PENG; Chang JIANG (天地一体化信息网络)
Based on the essence of satellite internet, the development status of satellite internet industry from three aspects of evolution path, global deployment and industrial chain was introduced. The operation mode of foreign satellite internet companies. was analyzed On this basis, combined with the network characteristics of the space-integrated-ground information network, and aimed at its basic business, the operation mode of the space-integrated-ground information network was proposed. Finally, the development suggestions of the application and operation of the space-integrated-ground information network were given.